Validity & reliability of cephalometric measurements in traditional versus digitized cephalometry (Mustansiria Dental Journal, 2018)
Aim: Film digitization is generally used to prevent potential damage or loss oforiginal films. The method of film processing has been changing from wet to dryprocessing due to recent trends toward digitization of medical imaging.Materials & Methods: 50 Lateral cephalometric radiograms were used in this study.All radiographs were viewed under standardized conditions& traced. Elevenlandmarks were selected to calculate 12 variables (9 angles&3 linearmeasurements).These traced radiographs were photographed when digitized using scan jet scanner &the same variables were measured using Dimaxis pro\ classic imaging software.Results: There were no statistically significant differences between traditional&digitized Linear & angular measurements except for upper incisor-Frankfortplane angle & upper incisor-lower incisor angle.Conclusion: Angular & linear measurements in digital images were comparable withthat of original radiograph & are clinically acceptable. This will substantiate thebenefits of digitized cephalometry in term of reliability of cephalometric analysis.